Modeling of wind generators for power flows and dynamic simulations - Castro González, Luis Miguel (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
The research reported in this thesis develops in the realm of wind power generation, addressing the timely research question of the impact that the installation of wind parks will bring upon the electrical power grid. This is of paramount importance because worldwide installed wind capacity has surpassed this year the 280 Giga-watt mark, out of which, China, USA and Germany together have more than 160 GW; it is quite clear that the global wind generation growth rate will continue to rise in the coming years. It is against this background of rapid growth of wind farm installations that the quest for developing versatile and efficient models of wind generators has been carried out. The two most popular types of generators have received research attention, namely, the fixed-speed and variable-speed wind generators. Their main operational characteristics have been captured in positive-sequence mathematical models, leading to comprehensive and reliable software tools for fundamental-frequency simulations. The electrical power grid is likely to experience frequency imbalances. Hence, the newly developed steady-state wind generator models are upgraded to include such an effect, with the improved models being capable of responding properly to the off-nominal frequency equilibrium point of the electrical network in the presence of power imbalances. Today’s wind parks employ the so-called doubly-fed induction generator (DFIG) technology owing to its higher energy throughputs and degree of controllability. A comprehensive model of DFIG is reported in this thesis for both steady-state and dynamic operating regimes. The associated back-to-back HVDC link using voltage source converters (VSC) is modeled by using a suitable assembly of electric circuit elements which encapsulates with a high degree of fidelity the steady-state and dynamics of the VSCs.

La investigación que se presenta en esta tesis se desarrolla en el ámbito de la generación de energía eólica, frente a la pregunta oportuna de los efectos que la instalación de parques eólicos traerá sobre la red eléctrica. Esto es de suma importancia, ya que la capacidad eólica instalada en todo el mundo ha superado este año la marca de los 280 GW, de los cuales, China, EE.UU. y Alemania juntos cuentan con más de 160 GW; es bastante claro que la tasa de crecimiento global de generación eólica continuará aumentando en los próximos años. Es en este contexto de rápido crecimiento de las instalaciones de parques eólicos en que la investigación para desarrollar modelos de generadores eólicos versátiles y eficientes se ha llevado a cabo. Los dos tipos más populares de generadores han sido investigados, es decir, los aerogeneradores de velocidad fija y de velocidad variable. Sus principales características de funcionamiento han sido capturadas en los modelos matemáticos de secuencia positiva, dando lugar a herramientas de software fiables y completas para simulaciones a la frecuencia fundamental. La red de energía eléctrica es propensa a experimentar desviaciones de frecuencia. Por lo tanto, los modelos recientemente desarrollados de aerogeneradores para análisis de estado estacionario son mejorados para incluir tal efecto, siendo capaces de responder adecuadamente al punto de equilibrio fuera de la frecuencia nominal de la red eléctrica en presencia de desbalances de potencia. Muchos parques eólicos actuales emplean generadores de inducción doblemente alimentado (GIDA), debido a sus altos rendimientos energéticos y grado de controlabilidad. Un modelo integral de GIDA se reporta en esta tesis para los regímenes de estado estacionario y dinámico.
Facultad de Ingeniería Eléctrica. Doctorado en Ciencias en Ingeniería Eléctrica
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3349; info:eu-repo/classification/cti/7; FIE-R-D-2013-2043; Modelado; Generadores eólicos; Energía